Software development practices and problems in Malaysian small and medium software enterprises: A pilot study - Almomani, M.A.T. (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper presents an empirical study that investigates Software Process Improvement (SPI) current practices amongst software development Small and Medium Enterprises (SMEs) in Malaysia. The empirical study determines the current practices of adoption of SPI and related problems. Six Malaysian software development SMEs were involved in the empirical study. The results of the study showed that the level of adoption of Software Process Improvement in Malaysian software development SMEs is still very much at the low level. Other organisational, software development and project issues were identified as contributing to the low level of SPI adoption in Malaysia. Â© 2015 IEEE.